Uma nova arquitetura para provisão de QoS utilizando enxame de partículas em redes WiMAX fixas - Dosciatti, Eden Ricardo (2015)
Technological advances in recent years have led to a growth in the user base using communication networks, especially with multimedia services such as IPTV, video conferencing and VoIP. As these services require more resources and generate a great demand on the network infrastructure, each user must have their applications dealt with in accordance with certain priorities, to provide an acceptable level of service. Under this assumption, the communication networks for wireless broadband, based on the IEEE 802.16 standard, also known as WiMAX, can meet the various demands of end users, the need for access to data at all times and in any place and the connectivity efficient broadband, offering excellent tredeoff for the end user by enabling high data transmission capacity at a relatively low cost of deployment. The provision of quality services is a very important factor for the performance of communication networks for that, the scheduling mechanisms, admission control connections and traffic policing, must be present. However, the IEEE 802.16 standard specifies only policies of how these mechanisms should be implemented, but does not define how to implement them. This research aims to present a new architecture for uplink traffic, the WiMAX network base stations, with provision of quality services through the particle swarm optimization metaheuristic to calculate the frame duration, allowing to find an ideal value, providing a better allocation of network users.